Intraoperative Ultrasonography in Resection of Diffuse Glioma - Ahmadi, Sayedali; Safari, Said; Chardoli, Mojtaba; Mirsalehi, Marjan (International Clinical Neuroscience Journal, 2021)
Diffuse glioma is a primary brain tumor that originates from glial supportive cells and is the most common type of intra-axial brain tumor. Open tumor resection is the first step in the treatment of diffuse gliomas. The extent of resection (EOR) directly influences clinical outcomes in glioma surgery. However, resection of diffuse glioma is encountered with the problem of macroscopic and even microscopic similarity of normal brain and tumor. Furthermore, maximizing EOR requires attention because a mistake in identifying and preserving normal brain regions in complete resection can lead to catastrophic complications.